2019
DOI: 10.1080/15532739.2019.1693472
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of transgender and non-binary children and young people and their parents in healthcare settings in England, UK: Interviews with members of a family support group

Abstract: The experiences of transgender and non-binary children and young people and their parents in healthcare settings in England, UK: interviews with members of a family support group Background: Transgender and non-binary children and young people and their parents in England, UK are poorly served across a range of healthcare settings.Whilst UK equalities legislation and international guidance on transgender healthcare pathways protects this group from discrimination and mandates an affirmative approach, services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0
26

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(103 citation statements)
references
References 38 publications
5
72
0
26
Order By: Relevance
“…Schools need to work on educating staff and, where possible, parents, as well as students (Carlile 2020). It was evident in our previous work (Carlile and Paechter 2018) that even primary school students could have more knowledge of trans issues than their teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools need to work on educating staff and, where possible, parents, as well as students (Carlile 2020). It was evident in our previous work (Carlile and Paechter 2018) that even primary school students could have more knowledge of trans issues than their teachers.…”
Section: Discussionmentioning
confidence: 99%
“…However, while there is considerable research on those trans young people identifying across a gender binary, i.e. as male or female (Paechter 2020;Carlile 2020;Edwards-Leeper, Liebowitz, and Sangganjanavanich 2016;Ehrensaft 2012;Ehrensaft et al 2018;Manning et al 2015;Marguerite 2018;Martino, Kassen, and Omercajic 2020;McCann et al 2019;Meyer and Leonardi 2018;Neary 2018;Pleak 2009;Price Minter 2012;Pyne 2014;Zucker 2019), comparatively little is known about those children and young people who identify outside of this, as non-binary, agender, genderqueer or using other related terms 1 (Jones et al 2020), and even research reports that use such terms as 'gender creative' in their titles frequently focus only on young people identifying across a binary gender divide. Furthermore, we have found virtually no research about non-binary young people's experiences of schooling, though they are occasionally mentioned in publications about what happens to binary trans people in educational settings (Bradlow et al 2017;Evans and Rawlings 2019;Jones et al 2016;Rankin and Beemyn 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the articles were from North America. Six studies were conducted in the United States of America [63,[87][88][89][90][91], two studies were conducted in Canada [92,93], one study was Australian [94] and one study was conducted in the UK (United Kingdom) [95]. Eight out of ten studies were undertaken in the last 5 years.…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Experiences of such affirming responses have been related to high levels of satisfaction among young people and their families attending paediatric gender clinics (Inwards-Breland et al, 2019;Pullen Sansfaçon et al, 2019;Tollit, Feldman, McKie, & Telfer, 2019). In terms of limitations, research has identified a lack of understanding by healthcare professionals of transgender young people's needs, discrimination, misgendering, and a lack of training about gender diversity (Carlile, 2020;Corliss et al, 2007;Eisenberg, McMorris, Rider, Gower, & Coleman, 2020;Goldenberg et al, 2019;Gridley et al, 2016;Guss et al, 2019;Heard et al, 2018;Strauss et al, 2017;Temple Newhook, Benson, Bridger, Crowther, & Sinnott, 2018). Such lack of understanding on the part of healthcare professionals can lead to transgender young people and their parents foregoing care (Clark, Veale, Greyson, & Saewyc, 2018;Goldenberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%